Behavioural responses to heat in desert birds: implications for predicting vulnerability to climate warming. Issue 1 (December 2016) - Smit, B.; Zietsman, G.; Martin, R.; Cunningham, S.; McKechnie, A.; Hockey, P.
Abstract Background Temperature increases associated with climate change pose a substantial threat to arid-zone bird species. However, predicting vulnerability to high temperatures using species-specific, mechanistic data, and assessing how this varies within and among species, is complex, time consuming and expensive. Using the bird community of the southern Kalahari Desert, we investigated whether interspecific variation in heat dissipation behaviour (HDB) thresholds could provide an index of vulnerability to high temperatures. We fitted logistic regression models to presence/absence data for behaviours as a function of air temperature (T air ) in order to determine, for each species, theT air at which panting and gular flutter (pant 50 ), wing-drooping (wing 50 ), resting (rest 50 ) and shade-seeking (shade 50 ) responses occurred in 50 % of instances. Results We show thatpant 50 (n = 30 species) is higher in species that 1) are smaller, 2) maintain low activity levels at highT air s, and 3) rely mostly on food as their water source (i.e. non-drinking species) — the only predictor variable to remain significant in phylogenetically-independent analyses. Likepant 50, wing 50 (n = 30 species) was negatively correlated with body mass, but did not vary systematically with other organismal traits. There was no systematic variation inshade 50 (n = 33 species) orrest 50 (n = 14 species) values. Conclusions Our findings suggest that evaporative cooling demands are relatively higher in larger birds and could limit activities (such as foraging) atT air s exceeding 30 °C, while the trade-off between thermoregulation and sustaining activity levels appears less pronounced in smaller species. Kalahari species that do not drink regularly show a relatively greater dependence on wing-drooping compared to panting/gular flutter, probably resulting from selective pressures to reduce evaporative cooling demands in an arid environment with scarce surface water. Two key questions remain to be answered to confirm whether variation in HDB thresholds provides an opportunity for rapid assessment of vulnerability to high temperatures in avian species from hot, arid environments. First, what are the relationships between HDB patterns and body temperature regulation? Second, is heat dissipation effort indicative of dehydration risk?